A two-stage voltage control method for distribution network integrated with complex electric vehicle clusters - Xin FANG; Juan LI; Yubo YUAN; Xiaodong YUAN (电力工程技术)
With the accelerating popularization of photovoltaics （PVs） and electric vehicles （EVs），distribution networks are facing issues such as voltage violations and voltage fluctuations. On the one hand，conventional voltage regulation resources are featured by slow response and limited lifespan，making them unable to rapidly respond to the temporary voltage issues caused by PVs and EVs. On the other hand，EVs and PVs interact with the power grid through charging stations and inverters，and their fully controllable power converters are capable of adjusting their operating settings in real time，making EVs and PVs ideal resources for reactive power-based voltage support. To fully leverage the reactive power support capabilities of EVs and PVs，a two-stage control scheme for the voltage regulation in distribution networks is proposed，including a day-ahead control stage and an intraday control stage. The day-ahead control stage provides a day-ahead operational scheduling of on-load tap changers and capacitor banks through global optimization algorithms to avoid potential voltage violation issues. The intraday control stage dynamically adjusts the reactive power output of EVs and PVs based on their real-time operating states，minimizing voltage deviations and fluctuations in the distribution network through reactive power compensation. Finally，the effectiveness of the proposed two-stage control method for voltage regulation in distribution networks is verified via case studies on a modified IEEE 123-bus test feeder. The simulation results show that the reactive power compensation capabilities of EVs and PVs can improve the voltage distribution in the distribution network to some extent.